GEOREFERENCING A COLD CASE VICTIM WITH LEAD, STRONTIUM, CARBON, AND OXYGEN ISOTOPES. Issue 1 (May 2014) - Kamenov, George D.; Kimmerle, Erin H.; Curtis, Jason H.; Norris, Darren; Kimmerle, Erin H.
<x xml:space="preserve">Abstract</x> Two men walking across a bridge along highway I‐75 found a young woman's body floating in the water below. This 1971 case has since become known as the "Little Miss Panasofkee" case. It is still an open homicide, for which neither the victim nor the perpetrator have been identified. Throughout the United States, thousands of similar cases remain open. The medicolegal communities work on these cases, as the years pass, applying new scientific methods and following new leads as they can be developed. As the years pass, the priorities of the investigations often shift. In any homicide investigation the goal is to solve the murder and bring the perpetrator to justice. While this is still true for long‐term open or cold cases, the needs of families to know the truth, find and bury remains, and find closure outside of criminal trials become increasingly important. In the case study presented here, we reanalyzed the biological profile of the decedent, created a new facial approximation and imaging for visualization of personal evidence, and analyzed samples of hair, bone, and enamel for Sr, Pb, C, N, and O isotopes to decipher a geographical place of origin for the decedent. Hair data show a shift from lighter to heavier C isotopic values indicating a diet change from more grain‐based (hair tip) to more corn‐based (hair root) diet. Oxygen isotopes in teeth show relatively heavy isotopic values suggesting southern geographical origin near a major water basin. Lead isotopic data for teeth and bone samples show relatively low‐radiogenic values suggesting that the victim was born and raised in Europe. There is shift to low 87Sr/86Sr from first to third molar and bone indicating possible migration and dietary change. Taken together, the radiogenic and stable isotope data indicate that the decedent was foreign born. The shift in the hair C isotopes suggests that the victim arrived in Florida/United States between 2 and 12 months before she was murdered. The Pb isotope data suggest European origin. Considering all of the chemical data, including Pb concentrations and Pb, Sr, O, and C isotope analyses on teeth, rib, and hair samples, we can suggest that the victim was most likely a foreigner from southeastern Europe, possibly Greece. The methods used here and the impact of these methods for developing new leads for investigators decades later are discussed and provide new avenues of investigation for other unsolved cases.